OPTIMAL MILK DISPOSAL EQUIPMENT DESIGN IN BOTTLE WITH ERGONOMICS APPROACH - Mujiono, Mujiono; Sujianto, Sujianto; Utomo, Addy (Journal of Sustainable Technology and Applied Science (JSTAS), 2020)
The results of the observation conducted by the research team at the milk processing company in the waste, the phase of waste destruction through the stage of one of them is the disposal of milk from the bottle is still using the manual tool when the bottle hole and pour the milk fluid into the tub. The milk disposal time in the bottle can be optimised with ergonomic tool design process. The meaning of ergonomic design is the design of a tool that generates a working system using the size of Anthropometri, while the research is focused on ergonomic tool design that can be used by the operator with the effective efficient, safe and comfortable result. With the stage conducted by the research team was conducting surveys, study of literture, data collection, formulating problems, analyzing and outdoor that is targeted is optimal model design tool using size anthropometri with height of shoulders when standing along the 138.5 cm, reach of the fore hands 72cm, the range of the side hand of 71cm, the height of the elbow when standing 104 cm and the knee height when standing 49 cm by saving the discharge time by 37%.